2006
DOI: 10.1186/1743-0003-3-14
|View full text |Cite
|
Sign up to set email alerts
|

A radial basis classifier for the automatic detection of aspiration in children with dysphagia

Abstract: BackgroundSilent aspiration or the inhalation of foodstuffs without overt physiological signs presents a serious health issue for children with dysphagia. To date, there are no reliable means of detecting aspiration in the home or community. An assistive technology that performs in these environments could inform caregivers of adverse events and potentially reduce the morbidity and anxiety of the feeding experience for the child and caregiver, respectively. This paper proposes a classifier for automatic classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 46 publications
0
36
1
Order By: Relevance
“…4 It has been applied in several fields, 2,6 including the analysis of swallowing vibration signals. 7,19,20 The following steps can thus be taken to analyze the stationarity of a time series with the reverse arrangement test 4,7 :…”
Section: Autoregressive Modeling Of Data Acquisition Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…4 It has been applied in several fields, 2,6 including the analysis of swallowing vibration signals. 7,19,20 The following steps can thus be taken to analyze the stationarity of a time series with the reverse arrangement test 4,7 :…”
Section: Autoregressive Modeling Of Data Acquisition Systemmentioning
confidence: 99%
“…39,47 An alternative approach for a noninvasive assessment of swallowing disorders is swallowing accelerometry, 41,40 a technique that involves an accelerometer placed on the neck to monitor vibrations associated with swallowing activities. Although single-axis accelerometers were traditionally used, 7,12,19,42 recent contributions showed that dual-axis accelerometers yield more information and enhance analysis capabilities, 20,46 likely because of the two-dimensional movement of the hyoid and the larynx during swallowing. 18,15 Even though accelerometry is becoming a valuable technique for the assessment of swallowing difficulties, some fundamental issues remain unaddressed.…”
Section: Introductionmentioning
confidence: 98%
“…These variables have been used in previous studies of dual-axis accelerometry signals by Lee et al [34] and represent fundamental summary statistics and spectral features of the signal. For the present study, signal characteristics were computed separately for each of the 500 swallows and then averaged for each participant, for each swallow task (saliva and water), and for each axis (AP and SI).…”
Section: Discussionmentioning
confidence: 99%
“…Although a microphone can be used, the combination of an accelerometer and digital signal processing has been the recent focus of research and termed swallowing accelerometry [2,[13][14][15]. One accelerometry study has shown a significant correlation between peak neck vibration and maximum hyolaryngeal excursion [3], which is a vital biomechanical component of airway protection during swallowing [16].…”
Section: Introductionmentioning
confidence: 99%
“…pulse oximetry [1], neck vibrations [2,3], cervical auscultation [4], surface electromyography [5], or nasal airflow [6]). Such signal modalities are attractive due to their low cost, easy-to-attach sensors, and portability.…”
Section: Introductionmentioning
confidence: 99%